(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
The utilization of porous asphalt mixtures has become increasingly important. This type of pavement has been used in many developed countries for many years with the addition of by-products to reduce the consumption of aggregates in road construction. Recently, the Malaysian Public Works Department (PWD) launched specifications for specialty mixtures and surface treatments, including porous asphalt. Therefore, this study was conducted to investigate the use of steel slag as a conventional aggregate replacement in porous asphalt mixtures. Two porous asphalt gradations, designated as Grade A and Grade B, were used in this study in accordance with the new specification – JKR/SPJ/2008-S4. Steel slag was chosen because its characteristics are quite similar to those of aggregates compared with other by-products such as crumb rubber, glass and many more. It was observed that steel slag aggregate meets all the criteria of the PWD specification except for the water absorption test. The samples of steel slag aggregate mixtures produced were tested for resilient modulus, rutting and permeability, which were later compared with conventional aggregate mixtures. The results show that there is a significant difference in terms of resilient modulus between the steel slag aggregate-based mixture and the conventional aggregate-based mixture. The same scenario was observed in the rutting test, where the steel slag aggregate mixture possesses a higher rut resistance. However the mixtures made from conventional aggregate had higher permeability values compared to the steel slag mixtures. It can be concluded that the use of steel slag could performed admirably during high traffic loading.